miR-148a regulation interferes in inflammatory cytokine and parasitic load in canine leishmaniasis - Rebech, Gabriela Torres [UNESP]; Bragato, Jaqueline Poleto [UNESP]; Costa, Sidnei Ferro [UNESP]; de Freitas, Jéssica Henrique [UNESP]; Dos Santos, Marilene Oliveira [UNESP]; Soares, Matheus Fujimura [UNESP]; Eugênio, Flávia de Rezende [UNESP]; Dos Santos, Paulo Sérgio Patto [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Public Library of Science (PLoS), 2023)
Canine leishmaniasis (CanL) is a severe public health threat. Infected animals mediate transmission of the Leishmania protozoan to humans via the sandfly’s bite during a blood meal. CanL progression depends on the degree of suppression of the immune response, possibly associated with microRNAs (miR), which can modulate mRNA translation into pro-teins and (consequently) regulate cell function. Increased miR-148a in splenic leukocytes (SL) of dogs with CanL was observed in previous studies, and in silico analysis, identified possible pathways involved in immune response regulation that are affected by this miR. Therefore, we evaluated the involvement of miR-148a in the regulation of TNF-α, IL-6, IL-12, IL-1β, iNOS, MHCII, CD80, CD3, T-bet, and GATA-3 transcription factors and their relationship with parasite load in SL of dogs with CanL. Splenic leukocytes obtained from healthy and diseased dogs were transfected with miR-148a mimic and inhibitor oligonucleo-tides. After 48 hours, expression levels of MHCII, CD80, iNOS, CD3, T-bet, and GATA-3 were evaluated by flow cytometry, and concentrations of TNF-α, IL-12, IL-6, and IL-1β were measured in culture supernatants by capture enzyme-linked immunosorbent assays. Trans-fection of SL with miR-148a mimics decreased iNOS levels in cells and TNF-α, IL-6, and IL-12 in the supernatants of cultured SL from CanL dogs. Interestingly, transfection with miR-148a inhibitor decreased parasite load in SL cells. These results suggest a direct or not regulatory role of this miR in the immune response to Leishmania infantum infection. We con-clude that miR-148a can modulate immune responses by regulating inflammatory cytokines during CanL. Our results contribute to understanding the complex host/parasite interaction in CanL and could assist the development of treatments.